Psychosocial impact of hearing loss on hearing-impaired patients and their spouses - Tengku Zam Zam, Tengku Zulaila Hasma; Dzulkarnain, Ahmad Aidil Arafat; Rahmat, Sarah; Jusoh, Masnira (IIUM Press, 2017)
Objective: To study the psychosocial impact of hearing impairment on hearing-impaired patients and their spouses. Materials and Method: In the first phase of the study, two questionnaires (HHIA and SOSHEAR) were initially translated using forward-backward translation techniques by four-panelists (2 panels for each level). The translated questionnaire was then reconciled and harmonized for cultural and content by the researchers and two expert panels before being piloted among 10 hearing impaired patients. At the present stage, the translated questionnaires were validated on 50 hearing-impaired subjects and 20 spouses with Cronbach’s α (for internal reliability) and Pearson’s correlation for (inter-item correlation). Subject were recruited from IIUM Hearing & Speech Clinic and several hearing centre in Kuantan and Selangor. In second phase, the validated questionnaires were later being given to the same participants (50 HI and 20 spouse) to determine the level of handicap for both population in regards to the hearing-impairment. For the third phase, 10 couples were recruited and the score for both questionnaires were analysed to study the relationship between hearing-impaired patients’ handicap level and their spouses’ third-party impairment. Results and Discussion: Cronbach’s α value were excellent for combined items in both questionnaires. There were a strong correlation between the total score of the combined items with each of the sub-scale scores for both HHIA-M and SOSHEAR-M. For the second and third phase, the data collection process were still ongoing and will be ready soon. Conclusion: The preliminary finding suggest the translated version of HHIA-M and SOSHEAR-M have the potential to be a reliable and valid tool to evaluate the hearing handicaps among hearing-impaired patients and their spouses in Malaysia. A large sample of subjects are needed for further evaluation to support this notions.